Sistema ininterrupto de energia de dupla conversão com integração do retificador e do inversor - Linard, Fabíola Maria Alexandre (2009)
This work presents the design, implementation and experimental results of double conversion 3 kVA UPS, input voltage of 220 V and output voltage of 110 V, with integration of the rectifier and the inverter stages. The system is composed of a rectifier and an inverter that employs the single-pole strategy on the modulation of the switches. The main characteristics of this system are: reduction of the number of the component; reduction of the conduction and switching losses in the semiconductors during the operation of the system and the topology contains a connection point from the power supply to the output stage. The design methodology and experimental results of an prototype are presented to validate the theoretical analysis and to evaluate system performance.